Pengaruh Metode Total Physical Response Terhadap Kemampuan Berbicara Pada Anak Usia 3-4 Tahun - zahrah ramadhani; Azizah Amal; Herlina (Jurnal Kajian Anak)
This study aims to determine the effect of Total Physical Response on speaking ability in children aged 3-4 years at TK Negeri Pembina, Bulukumba Regency. The research approach used is quantitative with a Quasi Experimental Design research type. The population in this study were children aged 3-4 years at TK Negeri Pembina, Bulukumba Regency. Sampling in this study used a purposive sampling technique. The sample in this study was 20 children, 10 children in the experimental group, 10 children as the control group. Data collection techniques in this study were documentation, tests and observations. Data analysis techniques in this study consisted of descriptive statistics and non-parametric analysis. Based on the results of the Wilcoxon sign rank test, the sig value was obtained. (2-tailed) 0.005 <0.05 then H0 is rejected and H1 is accepted, namely there is a difference in the average level of speaking ability in children aged 3-4 years at TK Negeri Pembina, Bulukumba Regency.